(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The Bottaccione section (Umbria-Marche Basin, central Italy) was analyzed for calcareous nannofossil and planktonic foraminiferal biostratigraphy across the Santonian-Campanian boundary interval to achieve a high-resolution and updated zonation directly calibrated with magnetostratigraphy. Several calcareous plankton events were detected, including zonal markers and additional potential biohorizons. The base of magnetochron C33r, proposed for placement of the base of the Campanian, lies between the first occurrence of Aspidolithus parcus parcus and the last occurrence of Dicarinella asymetrica in the Bottaccione section. The literature survey indicates that these events were found in the Santonian-Campanian boundary interval at supraregional scale and, may be used to confidently approximate the base of the Campanian.